Development of an Anti-Bleeding Agent for Recombinant Hirudin Induced Skin Bleeding in the Pig - Dickneite, Gerhard; Nicolay, Uwe; Friesen, Heinz-Jürgen; Reers, Martin (Thrombosis and Haemostasis, 1998)
Recombinant hirudin (rH) is a highly specific thrombin inhibitor which is under clinical investigation for various thrombotic disorders. However, one of its potential risks during clinical use might be hemorrhage, especially when combined with other agents interfering with the coagulation system like antiplatelet or fibrinolytic agents. In this experimental study we investigated whether Haemate, a von Willebrand Factor (vWF) and factor VIII containing product, could correct rH/aspirin induced bleeding in an experimental pig study. Skin bleeding time was evaluated in three open, placebo-controlled, randomized studies following comparable designs. A total of 62 animals were given a short-term infusion of aspirin (20 mg/kg) followed by a three-hour infusion of a high or low dose (0.3 or 0.5 mg/kg/h) of rH. At cessation of rH infusion, animals were allocated to treatment with either Haemate (30 FVIII U/kg) or the recombinant factor VIII, Helixate, which is devoid of vWF. The skin bleeding time (SBT, given as times of baseline) as measured four hours after the start of the rH infusion was defined as the prospective endpoint.In study 1 (low dose rH + Haemate) 4 h SBT was 2.18 (placebo) and 1.61 (Haemate, p = 0.0111). In study No. 2 (high dose rH + Haemate) SBT was 2.58 in placebo and 1.73 in Haemate (p = 0.0001). No significant difference between placebo and treatment were detected in study No. 3 (low dose rH + Helixate). Haemate but not Helixate significantly decreased bleeding time as compared to placebo at termination of the study (7 hours) which was defined as the secondary endpoint. No effect on either aPTT nor rH plasma levels were observed with any of the study drugs. It was concluded that Haemate decreases excess bleeding induced by rH/aspirin treatment without altering rH’s anticoagulant effect.